1991
DOI: 10.1111/j.1524-4725.1991.tb03278.x
|View full text |Cite
|
Sign up to set email alerts
|

The Treatment of Benign Sebaceous Hyperplasia with the Topical Application of Bichloracetic Acid

Abstract: Sebaceous hyperplasia is a benign lesion that occurs commonly on the face of older individuals. A variety of treatment options have been described, including oral isotretinoin, electrodesiccation, CO2 laser surgery, cryosurgery, and shave excision with curettage. Problems have been noted with these approaches. These techniques are more complex, less effective, require more time, or are more likely to scar than the procedure we describe. The treatment of sebaceous hyperplasia with bichloracetic acid is describe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 5 publications
0
21
0
Order By: Relevance
“…The classical therapeutic concept for the treatment of sebaceous gland hyperplasia in- cludes cryotherapy, cauterisation, topical drugs, or surgical excision [1][2][3]. These measures bear a considerable risk of posttherapeutic scarring or dyspigmentation, intra-and postoperative bleeding, and recurrence of the lesions [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The classical therapeutic concept for the treatment of sebaceous gland hyperplasia in- cludes cryotherapy, cauterisation, topical drugs, or surgical excision [1][2][3]. These measures bear a considerable risk of posttherapeutic scarring or dyspigmentation, intra-and postoperative bleeding, and recurrence of the lesions [18].…”
Section: Discussionmentioning
confidence: 99%
“…The established concepts for the treatment of sebaceous gland hyperplasia include cryotherapy, cauterization, excision of the lesion, and the topical application of drugs [1][2][3]. All of these strategies carry a considerable risk of disfigurative postoperative scarring or dyspigmentation.…”
Section: Introductionmentioning
confidence: 99%
“…Other procedures that have also been used include excision, electrocauterization, cryotherapy, shaving, curettage and cauterization with chemical agents used topically, although there is a risk of depigmentation or scarring with these latter options. [16][17][18][19][20][21][22][23][24][25] Many laboratory studies have shown the effect of androgens on the sebaceous glands. A review of the literature on several research models confirmed the effect of androgens in triggering the activity of the sebaceous glands and indicated which of these hormones may be implicated in triggering these glands.…”
Section: Introductionmentioning
confidence: 99%
“…66 The following therapies have been reported to be effective: photodynamic therapy, treatment with a 1450-nm diode laser, isotretinoin, bichloracetic acid, cryosurgery, electrodessication, and treatment with an argon laser, a pulsed-dye laser, and a carbon dioxide laser. [67][68][69][70][71][72][73][74][75][76][77][78][79] NSJ is a benign lesion that occurs most frequently on the scalp (59.3%) but has also been found on the face (32.6%), preauricular area (3.8%), neck (3.2%), and locations off the head and neck (1.3%). 80 It was originally described in 1895 by Jadassohn.…”
mentioning
confidence: 99%